Dimension formulas of the highest weight exceptional Lie algebra-modules - Zhang, Yupei; Luan, Yongzhi (AIMS mathematics, 2024)
Given a complex simple exceptional Lie algebra $ \mathfrak g $, let $ \mathscr V_λ $ be an irreducible finite-dimensional $ \mathfrak g $-module with highest weight $ λ $. We provide the precise dimension formula of $ \dim \mathscr V_{λ} $.